Certain Analytic Functions Defined by Generalized Mittag-Leffler Function Associated with Conic Domain - Adel A. Attiya; T. M. Seoudy; M. K. Aouf; Abeer M. Albalahi (Journal of Function Spaces)
In the present paper, we investigate and introduce several properties of certain families of analytic functions in the open unit disc, which are defined by q-analogue of Mittag-Leffler function associated with conic domain. A number of coefficient estimates of the functions in these classes have been obtained. Sufficient conditions for the functions belong to these classes are also considered.